Stability study of thymoquinone, carvacrol and thymol using HPLC-UV and LC-ESI-MS - Soliman Rabab M.; Abdel Salam Randa A.; Eid Basma G.; Khayyat Ahdab; Neamatallah Thikryat; Mesbah Mostafa K.; Hadad Ghada M. (Acta Pharmaceutica)
The aim of this study was to investigate the stability of three major antioxidants of Nigella sativa: thymoquinone (TQ), carvacrol (CR) and thymol (THY), under different stress conditions using HPLC and LC-MS/MS. Forced degradation for each compound was performed under different conditions, including oxidation, hydrolysis, photolysis and thermal decomposition. The results showed that both CR and THY were stable under the studied conditions, whereas TQ was not affected by acidic, basic and oxidative forced conditions but the effect of light and heat was significant. The degradation products of TQ were further investigated and characterized by LC-MS/MS. HPLC-UV method has been fully validated in terms of linearity and range, the limit of detection and quantitation, precision, selectivity, accuracy and robustness. The method was successfully applied to quantitative analysis of the principal antioxidants of Nigella sativa TQ, CR and THY in different phytopharmaceuticals.